Coronavirus Disease 2019 (COVID-19) Pandemic Lifestyle Changes May Have Influenced Small Bowel Microbial Composition and Microbial Resistance - Hosseini, Ava; Rashid, Mohamad; Leite, Gabriela; Barlow, Gillian M.; Parodi, Gonzalo; Sanchez, Maritza; Ayyad, Sarah; Pimentel, Maya L.; Morales, Walter; Weitsman, Stacy; Pimentel, Mark; Mathur, Ruchi (Digestive diseases and sciences, 2023)
Background The coronavirus disease 2019 (COVID-19) global pandemic necessitated many severe lifestyle changes, including lockdowns, social distancing, altered food consumption and exercise patterns, and extensive hygiene practices. These extensive changes may have affected the human gut microbiome, which is highly influenced by lifestyle. Aims To examine the potential effects of pandemic-related lifestyle changes on the metabolically relevant small bowel microbiome. Methods Adult subjects presenting for upper endoscopy without colonoscopy were identified and divided into two matched groups: pre-pandemic (February 2019–March 2020) and intra-pandemic (April 2021–September 2021, all COVID-19 negative). Duodenal aspirates and blood samples were collected. Duodenal microbiomes were analyzed by 16S rRNA sequencing. Serum cytokine levels were analyzed by Luminex FlexMap3D. Results Fifty-six pre-pandemic and 38 COVID-negative intra-pandemic subjects were included. There were no significant changes in duodenal microbial alpha diversity in the intra-pandemic vs. pre-pandemic group, but beta diversity was significantly different. The relative abundance (RA) of phylum Deinococcus-Thermus and family Thermaceae, which are resistant extremophiles, was significantly higher in the intra-pandemic vs. pre-pandemic group. The RA of several Gram-negative taxa including Bacteroidaceae (phylum Bacteroidetes) and the Proteobacteria families Enterobacteriaceae and Pseudomonadaceae, and the RA of potential disruptor genera Escherichia-Shigella and Rothia , were significantly lower in the intra-pandemic vs. pre-pandemic group. Circulating levels of interleukin-18 were also lower in the intra-pandemic group. Conclusions These findings suggest the small bowel microbiome underwent significant changes during the pandemic, in COVID-19-negative individuals. Given the key roles of the small bowel microbiota in host physiology, this may have implications for human health.